Introducción a los modelos clásicos de Recuperación de Información - Cacheda, Fidel (Revista General de Información y Documentación, 2009)
In this article main features of the classic models of information retrieval are smmarized. On the one hand, Boolean model is the simplest of these models, which implies that the quality of their results can be improved significantly. The probabilistc model provides a essential theoretical model in the filed of information retrieval, based on probability theory, trying to interpret all the uncertainty surrounding the process of IR. The vectorial model considers a document (an the query) as vectors of terms and calculate its similarity in an space of dimensions.